An Utilization of Palm Fuel Ash (POFA) and Ceramic Waste as Cement Materials Replacement in Concrete Production - Sheikh Khalid, Faisal; Natasya Mazenan, Puteri; Halim Abdul Ghani, Abdul; Bazilah Azmi, Nurul; Irwan Juki, Mohd; Shahidan, Shahiron; Haziman Wan Ibrahim, Mohd (International Journal of Engineering and Technology, 2018)
The consumption of agricultural and industrial wastes has grown rapidly across the world which leads to create large quantities of wastes. It reflects the problem of having a limited number of landfills due to a huge amount of waste produced. Therefore, the solution is recycle the agricultural and industrial wastes as one of the materials use in concrete. Agricultural and industrial wastes were selected as cement replacement in a concrete production. This study aims to investigate the concrete properties containing palm oil fuel ash (POFA) and ceramic tile wastes, such as workability, compressive and splitting tensile strength. The concrete mix design ratio was designed for concrete grade strength 30 and water cement ratio of 0.55. Testing for compressive strength was measured at 7 and 28 days and for tensile strength only at 28 days. This research finds that with combination of 5% POFA and 10% ceramic with 27.1 MPa for compressive strength and 2.5 MPa for tensile strength will be the optimum mix design to replace cement in concrete. This research helps to improve the knowledge, increase the level of environmental awareness and understanding the importance and recycling the construction waste generated.Â Â
Keywords: cement replacement; ceramic tiles waste; concrete; palm oil fuel ash (POFA); strength